2021 EFSA/IZSAM Animal Health Crisis Preparedness Exercise with Mediterranean Countries. Issue 8 (31st August 2021) - Calistri, Paolo; D'Albenzio, Silvia; Falconi, Annalisa; Pediconi, Ombretta; Johnson, Julia; Vincent, Andrew
Abstract: In July 2021, the European Food Safety Authority (EFSA) jointly devised, developed and delivered an online workshop on animal health crisis preparedness with IZSAM, focusing on Rift Valley fever (RVF). The overall training objective was to improve incident response collaboration between animal and public health authorities from multiple countries, using a 'One Health' approach. The 4 specific exercise learning objectives were to test and improve skills in: (a) outbreak investigation; (b) prevention of RVF outbreaks; (c) control of RVF outbreaks; (d) identifying and communicating to affected stakeholders about RVF outbreaks. Workshop content was jointly developed by EFSA, IZSAM and Instinctif Partners, with input from ECDC, FAO, OIE, WHO and EC DG SANTE. Twenty‐seven participants from 6 EU Member States (MSs) and 3 EU candidate countries attended the training, as well as 12 observers from 3 EU MSs and 3 international organisations. Plenary and working group activities extended across 3 days, preceded by the availability of an online RVF eLearning package developed by IZSAM. During the morning of Day One, 8 presentations were provided on various topics: (a) 'One Health'; (b) how EFSA and ECDC respond in urgent situations such as cross‐border threats of zoonotic disease emergences; (c) best practices in emergency risk communication; (d) examples of national‐level preparedness activities; (e) lessons learned from FAO RVF missions in Mauritania. From the afternoon of Day One to the morning of Day Three, a desktop discussion addressed the national and EU‐level responses that would ensue if RVF entered the EU, based on a fictional scenario. An additional presentation on Day Three reported on a recent RVF simulation exercise in Bulgaria. Concluding the event, subject matter experts provided interactive training on: (a) emergency response capacity building; (b) 'One Health'; (c) risk communication. The objectives of the event were achieved, based on recorded outcomes and feedback provided by participants in a series of online evaluation surveys. In addition, discussions during the event generated several practical recommendations for future enhancements and improvements.